IL-1β Genetic Polimorphism in Menopause Women as Periodontal Disease Risk Factor - Justine Tanjaya; Elza Ibrahim Auerkari (Faculty of Dentistry, Universitas Indonesia, 2013)
Periodontal disease is a disease with multifactorial etiology that can occur in postmenopausal women. Objective: This research aims to know the description of the genetic polymorphism of IL-1β in postmenopausal women in Indonesia as a risk factor for periodontal disease. Methods: This study is a descriptive study on 55 biological stored amples. Sample's extracted DNA was analysed for polymorphisms IL-1β+3954 using PCR-RFLP method with Taqα1 restriction enzyme digests then the result was electroforized. Research results were analyzed using chi square test. Results: The genotype CC frequency was 85.7%, CT 14.3%, and TT was absent in normal people. CC 86.5%, CT 8.3%, and TT did not exist in people who have periodontal disease. Conclusion: Genetic polymorphisms IL-1β in Indonesia's postmenopausal women is not a risk factor for periodontal disease DOI: 10.14693/jdi.v18i1.52